Análise dos impactos sócio-econômicos e ambientais das indústrias de calçados da cidade de Campina Grande - PB - França, Pollyanna Xavier Nunes (2006)
Since the appearance of the capitalist system until today, the industry has evolved acceleratingly as much in relation to industrial process as in types and quantity of product. Consequently, this has brought negative effects to the environment, because of high consumption of raw material, causing shortage some times, as well as causing the improper destination of the waste created during the production. This research had as objective to analyse the socio-economical and environmental impact of shoe industry of Campina Grande - PB. The study of the socio-economical aspects aimed to investigate the number of companies, functional insertion condition, that is, formal and informal conditions of the industries, number of jobs, income, among others. The study of environmental aspects investigated the methods of treatment, the final disposal of the solid waste of different kinds and quantities. The analysis of these parameters was done with data collection through questionnaire, in each company belonging to sampled universe, for future tabulation. After careful analysis of the data it can be concluded that in this branch of the industrial activity, there exists little concern with protection of the environment, seeing that a major part of the solid waste produced by the industrial activity is destined to the open dumping sites. This situation demonstrates the necessity for working with environmental management tools which may reduce the environmental impacts by this industrial sector. In relation to socio-economical question, it can be noticed that this kind of industrial activity, specifically the case studied, still absorbs a large number of labor, in spite of the significant presence of informal activity and low payment offered.